Literature Review: Effects of Turmeric for Reducing Lipid Profiles - Fadillah, Muh Alif; Indarwati, Rezky Putri; Nur, Muh Jabal (Newinera Publisher, 2024)
This literature review is a collection of several journals which aims to determine the effect of turmeric (Curcuma longa) on reducing lipid profiles, with emphasis on cholesterol and triglyceride levels. Turmeric is a daily food ingredient that is easy to find and has many good effects on the body, one of which is anti-inflammatory and anti-hypercholesterolemia. Hypercholesterolemia is a condition where the total cholesterol level in the body exceeds normal and can increase the risk of atherosclerosis. Curcumin is one of the active compounds in turmeric which has the function of reducing total cholesterol, LDL cholesterol, triglycerides which cause atherosclerosis and curcumin also increases the production of HDL cholesterol which helps protect against excess cholesterol accumulation which can cause heart and blood vessel disease. Based on several literature reviews, it is reported that the effectiveness of reducing cholesterol levels starts from a dose of 1000 mg - 1500 mg/day. The main aim of this research is to determine the effectiveness and safety of using turmeric as a supplement in reducing lipid profile levels in humans. Through this research, it is hoped that it can provide information regarding the effectiveness of turmeric as an effective additional therapy in managing lipid profiles.